Schriften zu Kunst und Film - Anders, Günther (2020)
This volume contains previously unpublished writings and hardly known texts of the philosopher, writer and intellectual Günther Anders (1902-92) on art and film. The writings date from the 1920s and 1930s, from Andersʼ years in exile in Paris (1933-36) and the USA (1936-50), especially from his years in Hollywood (1939-43), as well as from the post-war period up to the 1950s. These writings from the authorʼs estate are not only an important source for art and cultural studies, but also put a new complexion on Andersʼ oeuvre, in particular on his famous criticism of mass media from the first volume of his main work "The Outdatedness of Man" from 1956 ("The World as a Phantom and Matrix").